Visualization of the internal globus pallidus: sequence and orientation for deep brain stimulation using a standard installation protocol at 3.0 Tesla - Nölte, Ingo; Gerigk, Lars; Al-Zghloul, Mansour; Groden, Christoph; Kerl, Hans Ulrich (Acta neurochirurgica, 2012)
BACKGROUND: Deep-brain stimulation (DBS) of the internal globus pallidus (GPi) has shown remarkable therapeutic benefits for treatment-resistant neurological disorders including dystonia and Parkinson's disease (PD). The success of the DBS is critically dependent on the reliable visualization of the GPi. The aim of the study was to evaluate promising 3.0 Tesla magnetic resonance imaging (MRI) methods for pre-stereotactic visualization of the GPi using a standard installation protocol. METHODS: MRI at 3.0 T of nine healthy individuals and of one patient with PD was acquired (FLAIR, T1-MPRAGE, T2-SPACE, T2*-FLASH2D, susceptibility-weighted imaging mapping (SWI)). Image quality and visualization of the GPi for each sequence were assessed by two neuroradiologists independently using a 6-point scale. Axial, coronal, and sagittal planes of the T2*-FLASH2D images were compared. Inter-rater reliability, contrast-to-noise ratios (CNR) and signal-to-noise ratios (SNR) for the GPi were determined. For illustration, axial T2*-FLASH2D images were fused with a section schema of the Schaltenbrand-Wahren stereotactic atlas. RESULTS: The GPi was best and reliably visualized in axial and to a lesser degree on coronal T2*-FLASH2D images. No major artifacts in the GPi were observed in any of the sequences. SWI offered a significantly higher CNR for the GPi compared to standard T2-weighted imaging using the standard parameters. The fusion of the axial T2*-FLASH2D images and the atlas projected the GPi clearly in the boundaries of the section schema. CONCLUSIONS: Using a standard installation protocol at 3.0 T T2*-FLASH2D imaging (particularly axial view) provides optimal and reliable delineation of the GPi.
Gesehen am 05.04.2018